White matter hyperintensity burden and infarct volume predict functional outcomes in anterior choroidal artery stroke: a multimodal MRI study - Gao, Weiwei; Wang, Mingyang; Lin, Jianzhong; Huang, Junyi; Cai, Lijuan; Chen, Xingyu; Zhu, Renjing (Frontiers in Neuroscience, 2025)
ObjectiveTo investigate the relationship between white matter hyperintensity (WMH) burden and infarct volume with functional outcomes in patients with anterior choroidal artery (AChA) territory infarction.MethodsThis retrospective cohort study included patients with AChA territory infarction admitted to two comprehensive stroke centers between September 2018 and September 2024. WMH burden was assessed using the Fazekas visual rating scale and an automated volumetric quantification method based on lesion prediction algorithms. Acute infarct volume was precisely measured using fully automated threshold segmentation. Poor functional outcome was defined as a modified Rankin Scale (mRS) score ≥3 at 90 days. Associations were evaluated using multivariable logistic regression models with stepwise adjustment for confounders, and predictive performance was assessed using receiver operating characteristic curve analysis. Restricted cubic spline (RCS) regression was employed to explore non-linear associations, followed by piecewise regression analysis based on threshold effects.ResultsA total of 216 patients were included, of whom 73 (33.80%) had poor functional outcomes at 90 days. After adjusting for potential confounders, both WMH burden and infarct volume were independently associated with poor functional outcomes at 90 days, with infarct volume demonstrating superior predictive performance (AUC: 0.80 vs. 0.67). For each 1-mL increase in WMH volume, the risk of poor outcomes increased by 2% (adjusted OR = 1.02, 95% CI: 1.01–1.03, p = 0.032). RCS analysis revealed a non-linear association between infarct volume and poor outcomes, with a threshold of 2.7 mL. When infarct volume was below this threshold, each 1-mL increase in infarct volume was associated with a 5.31-fold increased risk of poor outcomes (adjusted OR = 5.31, 95% CI: 3.07–9.73; standardized OR = 3.03, 95% CI: 2.11–4.53).ConclusionIn patients with AChA territory infarction, both WMH burden and infarct volume can independently predict functional outcomes at 90 days. Infarct volume exhibits a non-linear association with outcomes, with a critical threshold of 2.7 mL identified.